Methylene Blue Sorption Equilibria on Hydroxylated Silica Surfaces as Well as on Carbon–Silica Adsorbents (Carbosils) - V.V. Yanishpolskii; J. Skubiszewska-Zieba; R. Leboda; V.A. Tertykh; I.V. Klischar (Adsorption Science & Technology)
The adsorption properties of hydroxylated silica gel as well as carbon–silica adsorbents (Carbosils) containing 5 and 18 w/w% carbon, both treated hydrothermally (with hydrogen peroxide solution) (HTT samples) and untreated, towards Methylene Blue (MB) were compared. The equilibrium adsorption of MB solutions of 6.5–7.0 × 10 −4 mol/l concentration and its dependence on pH were studied. At this concentration, ca. 30% of the adsorbent surfaces investigated were covered with MB molecules under optimal adsorption conditions. The presence of carbon deposits on the silica surface did not lead to a decrease in the adsorption capacity of Carbosils relative to that of hydroxylated silica. However, such deposits increased the resistance of the adsorbent towards the action of alkalis. Oxidation of the carbon deposit in the HTT process caused a further increase in this resistance. Hence, the adsorption mechanism of MB at equilibrium in individual systems of the type investigated can differ significantly. On the one hand, this mechanism is associated with the differing behaviour of silica over a wide range of pH relative to treated and untreated Carbosils and on the other hand with the specific properties of MB.